第53次日本南極地域観測隊越冬報告2012-2013 - 石沢, 賢二; Ishizawa, Kenji (2015)
P(論文) 第53次日本南極地域観測隊越冬隊は，「南極地域観測第Ⅷ期6か年計画」の第2年次を担う隊として，2012年2月12日に第52次隊から昭和基地の運営を引き継いだ．南極観測船「しらせ」が厚い海氷と積雪に阻まれ接岸できなかったため，燃料や物資の一部を基地に運ぶことができなかったが，越冬隊の観測・設営活動に大きな支障はなかった．重点研究観測として「南極域中層・超高層大気を通して探る地球環境変動」に基づき，南極大気の総合観測を実施した．設営関連の基地設備はおおむね順調で，発電機の停電事故もなく，ブリザードによる大きな損害もなかった．また，隊員の健康もおおむね良好で手術を必要とする事故もなかった．越冬後半から4 名の隊員が第54 次夏隊とともにドームふじ基地までのトラバース旅行に参加し，天文観測などを行った．観測隊ヘリコプターなどを利用して「しらせ」航行ルート付近の積雪及び海氷厚測定を行い，「しらせ」にデータを提供したが，第54次隊でも接岸できなかった．2013年2月1日に越冬交代式を行い，第54 次越冬隊に基地運営を引き継いだ． The JARE-53 wintering party conducted the second year of the research and logistical program of the six-year plan of Japanese Antarctic Program Phase VIII following the handover from the JARE-52 wintering party on 12 February 2012. Because the icebreaker Shirase could not anchor at Syowa Station due to thick sea ice and snow, some of the fuel and supplies were left on the ship. However, the wintering activities were not affected by any major adverse events. JARE-53 conducted comprehensive observations of the Antarctic atmosphere as one of the prioritized observation projects named "Earth's Environmental Change Revealed by Observing the Antarctic Middle and Upper Atmosphere". Logistics facilities at the station experienced no major problems and the electricity generators performed reliably. There was no serious blizzard-related damage and no physical injuries to personnel during the wintering period. Four members undertook a round-trip traverse to Dome Fuji Station led by the JARE-54 summer party, carrying out astronomical observations and other tasks. Sea-ice thickness and snow depth were measured near the intended routes of the icebreaker Shirase; however, the vessel was again unable to anchor at the Station. JARE-53 handed over the operation of the station to JARE-54 on 1 February 2013. departmental bulletin paper